2009
DOI: 10.1542/peds.2008-0253
|View full text |Cite
|
Sign up to set email alerts
|

Altered Heart Rhythm Dynamics in Very Low Birth Weight Infants With Impending Intraventricular Hemorrhage

Abstract: OBJECTIVE-Intraventricular hemorrhage remains an important problem among very low birth weight infants and may result in long-term neurodevelopmental disabilities. Neonatologists have been unable to accurately predict impending intraventricular hemorrhage. Because alterations in the autonomic nervous system's control of heart rhythm have been associated with intraventricular hemorrhage after its development, we sought to determine if early subtle alterations of heart rhythm could be predictive of impending int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 45 publications
(48 reference statements)
0
23
0
Order By: Relevance
“…[42] We did not collect physiologic measures of the cerebral circulation. [43, 44] Injury to the white matter of the brain is an important cause of neurodevelopmental impairment; we did not evaluate magnetic resonance imaging studies to detect white matter injury. Finally, the incidence of multiple gestation pregnancies in white mothers was almost double that in African ancestry mothers in our study and that finding may have influenced the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[42] We did not collect physiologic measures of the cerebral circulation. [43, 44] Injury to the white matter of the brain is an important cause of neurodevelopmental impairment; we did not evaluate magnetic resonance imaging studies to detect white matter injury. Finally, the incidence of multiple gestation pregnancies in white mothers was almost double that in African ancestry mothers in our study and that finding may have influenced the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in HF power was proportionally less than that of the LF power between the Control group and the PDA group, leading to a decrease in LF/HF ratio from 5.52 ± 3.28 (Control group) to 2.74 ± 1.67 (PDA group), consistent with parasympathetic dominance. In children and neonates, major reduction in HRV power has been described in intracerebral haemorrhage [9], severe sepsis [10], RDS, the aftermath of Fontan open-heart surgery [11] and pulmonary stenosis [12]. The low HRV power observed in our study in preterm infants with PDA (i.e.…”
Section: Discussionmentioning
confidence: 43%
“…In this case, the short-term scaling exponent was defined over 4–15 beats, as aligned with similar observations of this data9 and similarly defined for heart rate variability analysis of preterm infants8. The long-term scaling exponent was determined across 15–50 beats.…”
Section: Methodsmentioning
confidence: 76%
“…In particular, one study showed that these differences could be detected using electrocardiogram data from the first 24 hours of life8. Variability of beat-to-beat systolic blood pressure and mean arterial pressure has also been shown to offer useful information in distinguishing infants who later developed IVH from those who did not9.…”
mentioning
confidence: 99%